2001
DOI: 10.1136/heart.86.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Long term results of mechanical prostheses for treatment of active infective endocarditis

Abstract: Objective-To analyse the long term results of mechanical prostheses for treating active infective endocarditis. Design-Prospective cohort study of a consecutive series of patients diagnosed with infective endocarditis and operated on in the active phase of the infection for insertion of a mechanical prosthesis. Setting-Tertiary referral centre in a metropolitan area. Results-Between 1975 and 1997, 637 cases of infective endocarditis were diagnosed in the centre. Of these, 436 were left sided (with overall mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…Congestive heart failure and embolism are the greatest predictive factors of prognosis in patients with infective endocarditis. [5][6][7][8][9][10] This patient was diagnosed as congestive heart failure of NYHA Class IV with vegetation observed both on the anterior and posterior mitral leaflets, both of which exceeded 10 mm, and emergency surgery was indicated although the infection was not controlled. Prognosis of the patient was not expected without surgery although she was also in a high-risk state with cardiac cachexia and thrombocytopenia due to ITP before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure and embolism are the greatest predictive factors of prognosis in patients with infective endocarditis. [5][6][7][8][9][10] This patient was diagnosed as congestive heart failure of NYHA Class IV with vegetation observed both on the anterior and posterior mitral leaflets, both of which exceeded 10 mm, and emergency surgery was indicated although the infection was not controlled. Prognosis of the patient was not expected without surgery although she was also in a high-risk state with cardiac cachexia and thrombocytopenia due to ITP before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Wos and colleagues showed that the risk of recurrent endocarditis was higher with bioprostheses than with mechanical valves (Wos, 1996). Guerra et al also found that the risk of endocarditis reinfection is very low with mechanical valves (Guerra, 2001). Homograft seems to be good choice in severe destructive prosthetic (Musci, 2010) or native (Klieverik, 2009) valve endocarditis with aorto-ventricular dehiscence caused by abscess.…”
Section: Active Infective Endocarditismentioning
confidence: 99%
“…Contrary to previous reports, there is no evidence that bioprostheses are less susceptible to recurrent infection than metallic valves. 14 The management of cardiac devicerelated IE is a new area and the best outcomes are achieved after close liaison between the cardiologist, cardiac surgeon and microbiologist. The most common pathogens are staphylococci (particularly S. aureus and S. epidermidis).…”
Section: Indications For Surgerymentioning
confidence: 99%